Nuove forme di storytelling di viaggio e promozione territoriale: Il racconto di BabyTrekking, influencer delle montagne - Bertoloni, Luca; Chieppe, Arianna (Mediascapes journal, 2023)
In this paper, starting from some considerations around the current mediscape, we propose an analysis of the discursive-enunciative strategies of the BabyTrekking brand, founded by the travel micro-influencer Azzurra Forti, and dedicated to tourist experiences in the mountains with children, mainly in the Dolomite area between Trentino Alto-Adige and Tyrol. The analysis deals with the methodologies used in media studies and in tourism, geography and communication studies, and is carried out by configuring the figure of Forti inside the universe of travel influencers and of influencer marketing, limiting her production – with particular reference to the audiovisual one – within the extended writing of the web, travel storytelling practices and digital stories of territorial promotion. The study shows that brand communication, thanks to the development of specific user generated contents, is configured as effective since it is supported by a synergy between the target and the portrait of destination; a synergy that, since it offers to the followers a new way to access tourist information, guarantees its reliability from visually authenticating practices, and from the solicitation of relational, friendly, and confidential elements by the influencer. In fact, Forti, posing as an ordinary person, allows the followers to walk virtually alongside her in mountain excursions, and, also intercepting some macro-trends of contemporary tourism, she manages to remain firm in the mediascape, gaining a specific space within a certain segment of tourists, towards she implements an effective influence activity in terms of territorial promotion.